Do Frequent Lactation Periods in Laboratory Rat Colonies Have a Negative Effect on Mothers' Care and Feeding of Themselves and Their Offspring? - Abdullah Kumral; Pembe Keskinoğlu; Defne Engür; Canberk Yılmaz; Osman Yılmaz (Laboratuvar Hayvanları Bilimi ve Uygulamaları Dergisi)
Laboratory rats are the second most preferred mammal species in experimental research. Do the frequent lactation periods of the female rats used in production in this study negatively affect the care of the offspring and themselves? For this purpose, the care of mother rats from a conventional outbred Wistar Albino rat colony for themselves and their offspring was monitored in two consecutive lactation periods. Mother rats successfully raised all their offspring in two lactation periods, mothers spent 85% of their daily life in the early phase of the two lactation periods (Post Natal-PN 1-8 days), 60% of their daily life in the mid-lactation phase (PN 9-18 days) and 60% of their daily life in the late lactation phase (PN 19-23 days) have been found to spend 30% of their daily lives with their offspring. While there was a significant difference in terms of the times that mother rats were with their babies in the early, middle, and late stages of the lactation period, the time they were separated from their babies and the frequency of separation (p< .001), no significant difference was found when the same stages of the two lactation periods were compared with each other (p> .05). Live weight change, feed consumption, and water consumption changes of mother rats in two lactation periods were compared and no significant difference was found. It was concluded that there was no negative effect on the care of mother rats and their offspring during frequent lactation periods.